2003
DOI: 10.1107/s1600536803027880
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxy-3,3′,4′,5′,7-pentamethoxyflavone (combretol)

Abstract: The structure of the title compound, C20H20O8, which was extracted from Rhodomyrtus tomentosa, confirms the connectivity and is consistent with the results from spectroscopy. The structure, notable for the crowded sequence of (3′,4′,5′) tri­methoxy substituents, is compared with that of its previously recorded analogue lacking the methyl at the 4′‐oxy­gen (two polymorphs), and with myricetin which lacks all O‐methyl­ation (cocrystallized with tri­phenyl­phosphine oxide). The latter, interestingly, has a dihedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The bond lengths and angles of the flavone ring system in (I) ( Fig. 1) are comparable to those of 5,3 0 -dihydroxy-3,7,4 0 ,5 0tetramethoxyflavone (Etti et al, 2005) and 5-hydroxy-3,7,3 0 ,4 0 ,5 0 ,-pentamethoxyflavone (Dachriyanus et al, 2004). As expected, rings A (C4a/C5-C8/C8a), B (O1/O2/C3/C4/C4a/ C8a) and C (C1 0 -C6 0 ) are planar, the dihedral angles between them being A/B = 2.37 (4) , A/C = 9.49 (3) and B/C = 7.20 (4) .…”
Section: Commentsupporting
confidence: 53%
“…The bond lengths and angles of the flavone ring system in (I) ( Fig. 1) are comparable to those of 5,3 0 -dihydroxy-3,7,4 0 ,5 0tetramethoxyflavone (Etti et al, 2005) and 5-hydroxy-3,7,3 0 ,4 0 ,5 0 ,-pentamethoxyflavone (Dachriyanus et al, 2004). As expected, rings A (C4a/C5-C8/C8a), B (O1/O2/C3/C4/C4a/ C8a) and C (C1 0 -C6 0 ) are planar, the dihedral angles between them being A/B = 2.37 (4) , A/C = 9.49 (3) and B/C = 7.20 (4) .…”
Section: Commentsupporting
confidence: 53%
“…Our metabolic profiling of trichome glands from S. habrochaites leaf identified three forms of O-methylated myricetin species: 3,7,3#-MeM, 3,7,3#,5#-MeM, and 3,7,3#,4#,5#-MeM. These three compounds have previously been shown to accumulate in tissues of several other plants (Stevens et al, 1995;Dachriyanus et al, 2004;Ariyanathan et al, 2010), but they have not yet been reported to be present in trichomes. By isolating individual types of glands, we were able to show that these compounds are found in three types of glandular trichomes, types 1, 4, and 6 (Fig.…”
Section: Characterization Of the Kinetic Parameters Of Shmomt1 And Shmentioning
confidence: 85%
“…Compounds 10 − 17 were revealed to be arjunolic acid ( 10 ), asiatic acid ( 11 ), 5,7,3′,5′-tetrahydroxy-3,4′-dimethyoxyflavone ( 12 ), combretol ( 13 ), 3′,5-dihydroxy-3,4,′5′,7-tetramethoxyflavone ( 14 ), pachypodol (5,4′-dihydroxy-3,7,3′-trimethoxyflavone) ( 15 ), quercetin 3,4′-dimethyl ether (5,7,3′-trihydroxy-3,4′-dimethoxyflavone) ( 16 ), and myricetin 3,3′,4′-trimethyl ether ( 17 ) by comparison of their NMR and MS data with those in the literature.…”
Section: Resultsmentioning
confidence: 99%